Early effect of box, triangular and trapezoidal Ge profiles for SiGe HBTs. (November 2017) - Xu, Xiaobo; Gu, Wenping; Quan, Si; Zhang, Zan; Zhang, Lin
Abstract: This paper deals with the Early effect of SiGe HBTs. Simple, analytical expressions are derived for forward and reverse Early voltages, considering different Ge profiles in the base, including box, triangular, and trapezoidal profiles. The SiGe parameters of the electron diffusion coefficient and the intrinsic carrier concentration are adopted to modify the traditional model. It is predicted that the triangular and box Ge shapes in the base of SiGe HBTs correspond to the best forward and reverse Early voltages, respectively.